The Implementation of Integrated One-Stop Service at Licensing Service Agency in Order to Improve Licensing Service to Society (Case Study On Business License Service At Investment And Integrated Licensing Service Agency (IILSA) Of Pasuruan City) - Priyani Dini Pramita; Siti Rochmah; Ratih Nur Pratiwi (Sekolah Pascasarjana Universitas Brawijaya, 2014)
This study discusses about the implementation of integrated one-stop licensing services related to service of SIUP, conducted by the Investment and Integrated Licensing Service Agency (IILSA) in Pasuruan City. In general there are any issues related to License for business activities, namely: the complicated procedures, high costs and legal uncertainty. To overcome this problem the government issued Permendagri number 24 of 2006 about Guidelines for the Implementation of One Stop Services. The focus of this study discusses the implementation of an integrated one-stop service, based on the rules associated with seeing some of the following elements: (1) executing actor (2) communication (3) resources (4) bureaucratic structure (5) the target group. This research used descriptive method with qualitative research approach. Activity of data analysis in this study consisted of data reduction, display and verification of data. The result of this research can be said that the implementation is done by IILSA of Pasuruan city has been good although there are a few things that need to be improved related to the internet connection is still an obstacle in the implementation of the operational in the delivery service for SIUP and also the lack of facilities and infrastructure available. Keywords: IILSA of Pasuruan City, Licensing Service, SIUP (Business License), Improve Service, The Implementation.